2016
DOI: 10.1177/0020872816633889
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating individual community assets in neighbourhood houses: Beyond the community-building tradition of settlement houses

Abstract: As a global movement, neighbourhood houses (NHs) are found in urban communities all over the world. Following the community-building tradition of early settlement houses, NHs have been actively nurturing and mobilizing community assets to serve the local community, but it is not known whether NHs have incorporated these assets in their infrastructure. This article reports the findings of a clearinghouse survey of 15 NHs in Metro Vancouver, Canada, which indicate that they nurtured community assets and incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Nonetheless, studies have also found that NHs have maintained a strong role in community building in many local communities (Hirota el al. 1997;Yan et al, 2009Yan et al, , 2016, particularly by connecting local residents (Yan and Lauer, 2008). As a place-based CSO, Neighbourhood House is part of a web of social services that tend to be institutionally isolated and fragmented.…”
Section: Settlement House As a Mechanism Of Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, studies have also found that NHs have maintained a strong role in community building in many local communities (Hirota el al. 1997;Yan et al, 2009Yan et al, , 2016, particularly by connecting local residents (Yan and Lauer, 2008). As a place-based CSO, Neighbourhood House is part of a web of social services that tend to be institutionally isolated and fragmented.…”
Section: Settlement House As a Mechanism Of Connectionmentioning
confidence: 99%
“…The emphasis on neighbourhood better reflects the place-based tradition of settlement house. As reflected in the studies of NHs in North America (Hirota et al, 1997; Koerin, 2003; Yan et al, 2016; Yan and Sin, 2010), situated in an urban neighbourhood within walking distance to most residents, most NHs are largely governed by local people. They are operated by a small team of paid staff in collaboration with a large number of volunteers who are mostly local residents.…”
Section: Introductionmentioning
confidence: 99%